The profile of the inclusive teacher in the secondary school: An exploratory investigation carried out at the Specialization Course for Educational Support Activities for Pupils with Disabilities at the University of Catania - Gulisano, Daniela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this research, the Author attempts to deepen and analyze the first results that emerged from an exploratory survey of a descriptive nature aimed at students / teachers of the Specialization Course for didactic support activities for pupils with disabilities of the University of Catania. in the academic year 2021/2022 with the aim of investigating the quality and professional skills of the inclusive teacher. Along this direction, 663 teachers / students of the secondary school of I and II degree were reached, currently engaged in specialization. This contribution presents the theoretical and methodological framework of the research and an initial description and analysis of some of the data collected.